Peran Literasi Budaya dan Kewargaan dalam Membina Sikap Toleransi Antar Siswa - Maylitha, Evi; Dewi, Dinie Anggraeni; Hayat, Rizky Saeful (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Cultural diversity in Indonesia indicates that Indonesia is a country that has many differences. These differences should be a binder between nations in Indonesia. Differences provoke the emergence of tolerance. Tolerance should be introduced as early as possible as a provision in the future. This study aims to determine the role of cultural and civic literacy in fostering tolerance between students. This research uses qualitative methods with literature review. Data collection through various books, articles, and other relevant references. The results of data analysis show that cultural and civic literacy is a fortress in people's lives to create a peaceful life with differences.